Graphite-doped cadmium oxide nanoparticles: structural modifications, dielectric enhancement, and percolation-driven electrical evolution - Kacmaz, Nafiz; Macit, Cevher Kursat; Gurgenc, Ezgi; Biryan, Fatih; Ilkilic, Cumali; Gurgenc, Turan (Springer, 2025)
This study comprehensively investigates the structural, morphological, and dielectric properties of pure Cadmium Oxide (CdO) and Graphite (Gr)-doped CdO nanoparticles synthesized via the sol-gel method. CdO nanoparticles were successfully doped with 1%, 5%, and 10% (wt) Gr, and their physicochemical characteristics were systematically analyzed using X-Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FT-IR), Field Emission Scanning Electron Microscopy (FE-SEM), and Energy Dispersive X-ray (EDX) analysis. XRD results confirmed the retention of the cubic crystal structure of CdO, with Gr doping inducing distinct peak shifts and intensity variations, highlighting successful incorporation of Gr at the atomic level, as evidenced by the characteristic peak at 26.4466 degrees (2 theta) corresponding to the (002) plane of graphite. FE-SEM and EDX analyses revealed the homogeneous formation of CdO nanoparticles on Gr sheets and a proportional increase in carbon content with higher Gr doping levels. Dielectric studies demonstrated that Gr incorporation significantly enhances both the dielectric constant and AC conductivity of the composites, with a notable percolation threshold observed at 5% Gr doping. The CdO-10Gr nanocomposite exhibited the highest dielectric constant (epsilon' = 34.58) and AC conductivity (sigma_ac = 6.62 x 10(-)(7) S/cm), surpassing pure CdO. The novelty of this work lies in the systematic optimization of Gr doping in CdO nanoparticles to tailor their dielectric and electrical properties, which is crucial for advancing next-generation electronic materials. These enhanced properties render the CdO-Gr nanocomposites highly promising for practical applications in electronic and optoelectronic devices, such as capacitors, supercapacitors, sensors, and microwave absorbers. This study thus provides valuable insights into the design of efficient, low-cost, and environmentally friendly nanocomposites for advanced functional devices.
Keywords: Cdo Nanoparticles; Graphene Oxide; Optical-Properties; Conductivity; Performance